2018
DOI: 10.1016/j.jvs.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Viabahn stent graft for the treatment of recurrent cephalic arch stenosis in hemodialysis accesses

Abstract: In treatment of a CAS, the Viabahn SG study group demonstrated superior target lesion primary patency and required fewer subsequent interventions compared with historic cohorts treated with angioplasty or angioplasty followed by BMS placement. Given the significant improvement in target lesion primary patency, future studies should challenge Viabahn SGs as a primary percutaneous treatment modality vs durable surgical alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 24 publications
0
51
1
1
Order By: Relevance
“…Cephalic arch stenosis affects up to 34% of dysfunctional brachiocephalic AVFs (Bennett et al 2015). The use of stents, in particular SGs, to treat recurrent cephalic arch stenosis has been increasing due to low primary patency rates of balloon angioplasty and an increasing body of evidence demonstrating superior patency rates of stents (Miller et al 2018;D'Cruz et al 2019). Despite appropriate sizing and accurate deployment of the Fluency SG, central stent migration may result in jailing of the axillary vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cephalic arch stenosis affects up to 34% of dysfunctional brachiocephalic AVFs (Bennett et al 2015). The use of stents, in particular SGs, to treat recurrent cephalic arch stenosis has been increasing due to low primary patency rates of balloon angioplasty and an increasing body of evidence demonstrating superior patency rates of stents (Miller et al 2018;D'Cruz et al 2019). Despite appropriate sizing and accurate deployment of the Fluency SG, central stent migration may result in jailing of the axillary vein.…”
Section: Discussionmentioning
confidence: 99%
“…Stent-graft (SG) placement for cephalic arch stenosis in dysfunctional dialysis access is an option for patients, and a recent systematic review suggests that it may be more durable in the short term compared to angioplasty alone (Miller et al 2018;D'Cruz et al 2019). Precise placement of SGs in the cephalic arch, particularly the terminal segment near or at the junction with the axillary vein, can be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Cephalic arch stenosis and occlusion are common in hemodialysis patients and are successfully treated with stent grafts with 60% primary patency and 98% secondary patency at 1 year (10). In 1 of the larger surgical studies, a comparison of 219 patients found that the 2-year patency was greater than 90% for cephalic vein transposition and bypass surgery and less successful, with 63% and 59% patency, for balloon dilation and bare metal stents (3).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the authors would likely use a self-expanding stent graft, such as a Viabahn (W. L. Gore, Flagstaff, AZ), which has the additional advantage of improved patency rates in the cephalic arch compared with angioplasty or bare metal stents. [7][8][9][10][11] Given the IFU warning against using the PTD in stents, case reports of stent-related complications are predictably difficult to find in the literature. Recent stent placement, poor wall apposition (more likely in fistulae than in grafts), and bare metal construction could all plausibly contribute to increased likelihood of stent entanglement with the fragmentation basket.…”
Section: Discussionmentioning
confidence: 99%